SISTEM INFORMASI AKUNTANSI, KINERJA NON-KEUANGAN DAN KINERJA KEUANGAN DI PERUSAHAAN KECIL: PENELITIAN EMPIRIS BERDASARKAN GENDER - Ickhsanto Wahyudi; Rezki Aulia; Tantri Yanuar Rahmat Syah; Agus Munandar; Agus Cholik (Jurnal Ilmiah Global Education, 2023)
AIS is a mandatory tool for managers to have a competitive advantage amidst rapid technological advances. Business competition is conducted based on financial as well as non-financial performance indicators. The research objective was to examine gender differences in the use of AIS and non-financial and financial performance measures by SMEs for better performance. AIS requirement, AIS capacity, and non-financial and financial performance are measured using a questionnaire. AIS alignment is measured by multiplying the AIS requirement items by the AIS capacity. The hypothesis was tested using multiple linear regression to determine the effect of AIS requirement and AIS capacity on AIS alignment and the effect of AIS alignment on SME financial and non-financial performance. Different tests are used to examine differences in AIS alignment based on gender and differences in financial and non-financial performance based on gender. AIS requirement and AIS capacities have a significant influence on AIS alignment. AIS alignment does not have a significant impact on SME non-financial performance or financial performance. Women have a more positive perception of the non-financial and financial performance of SMEs than men. There is no significant difference in perception between men and women regarding AIS alignment. Research suggestions include getting a larger and more representative sample of small companies. The research is expected to provide guidance for SMEs in choosing an appropriate AIS to face a competitive business environment and serve as a basis for further research